Delivering Road Safety in Nepal : Leadership Priorities and Initiatives to 2030 - World Bank (World Bank, Washington, DC, 2020)
Road crash deaths and injuries in Nepal have been on a sharp upward trajectory since the early 2000s. In fi scal year 2017–18, 2,541 road deaths were offi cially reported in Nepal, which is equivalent to a fatality rate of 8.59 per 100,000 population. In the same period, 4,144 serious injury and several minor injury victims were also offi cially reported. However, according to World Health Organization data the estimated fatality rate in 2016 was 15.9 per 100,000 population, which is nearly double the offi cial estimate. In 2016, vulnerable road users (pedestrians, cyclists, and motorcyclists) accounted for around 72 percent of all road fatality victims, among the highest levels in the region, with pedestrians accounting for half of these. Road deaths have a disproportionate impact on the young, working age population. About 40 percent of people killed on Nepal’s roads in 2017 –18 were less than 26 years old. In 2016, transport injuries were the second leading cause of death among men aged 15–49-years.